Implementasi Pembiasaan Pendidikan Islam dalam Membentuk Karakter Religius Siswa Sekolah Dasar: Implementation of Islamic Education Habituation in Forming the Religious Character of Elementary School Students - Fahmi, Muhammad Nahdi; Susanto, Sofyan (Pedagogia : Jurnal Pendidikan, 2018)
The era of globalization brings much impact on the lives of everyone from children, youth, adults and the elderly. Between positive and negative impacts, of course there are many negatives if we do not respond wisely. The role of character education in life is very important, especially religious education. With a strong religious education is also created a good human character. Based on the results of observation on elementary school students, there is a very poor problem related to their character. Character degradation is found in children of primary school age where they are easily affected by the negative influence of the development of the era. The purpose of this study is to describe the results of implementation of Islamic education in shaping the religious character of elementary school students. The method used in this research is action research. The subjects of this research are 5th grade students of SDN Tambakromo 2 of Ngawi Regency with a number of 25 people. The results of the study showed a significant change from the original 85% of children with character values below the average then after the action dropped to 13% of children who are still difficult to change their character. Of the 87% of respondents felt the habituation of Islamic education in life brought many changes in their religious character. Habits made include: carrying out morning exercises, memorizing letters in the Koran, praying in congregation, saying greetings, and saying politely. In monitoring all the habits, used diary daily activities.